2007
DOI: 10.1055/s-2007-981506
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Reduces Necrotic Flap Zones and Induces VEGF Expression in Animal Epigastric Skin Flap Model

Abstract: The effect of extracorporeal shock wave (ESW) therapy on skin flap survival and growth factor expression was investigated in a rat model using epigastric skin flap. Treatment and control groups each contained 20 animals. ESW effectively enhanced epigastric skin flap survival by significant reduction of areas of necrotic zones. At day 7 after the operation, necrotic zones of 4.2% were found in the ESW-treated group compared with 18.3% in the control group ( P < 0.01). Concomitantly, in tissue samples adjacent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 15 publications
(23 reference statements)
0
43
0
Order By: Relevance
“…Recently, ESWT was shown to be valuable for the treatment of chronic wound, such as bedsores [17], vascular and diabetic ulcers [18][19][20], burn wounds [21,22] and skin flaps [23]. However, these studies were limited clinical trials with low level of evidence [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ESWT was shown to be valuable for the treatment of chronic wound, such as bedsores [17], vascular and diabetic ulcers [18][19][20], burn wounds [21,22] and skin flaps [23]. However, these studies were limited clinical trials with low level of evidence [24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various research groups have focused on the angiogenic impact of shock waves (4,5,12,13). They have shown that ESWT up-regulates angiogenesis via mediators such as vascular endothelial growth factor (VEGF), endothelial nitric-oxide synthase, hypoxia-inducible factor 1a, and CD31 (4,5,14,15). ESWT was shown to augment the expression of proliferating cell nuclear antigen and the recruitment of fibroblasts and to down-regulate production of proinflammatory cytokines (16).…”
mentioning
confidence: 99%
“…The threshold to induce new bone growth is supposed to be between 0.16 mJ/mm 2 used in animal experiments Wang et al, 2003;Ma et al, 2007) and 0.62 mmJ/mm 2 in clinical studies (Rompe et al, 2001;Schaden et al, 2001). To induce vascular growth successfully in soft tissues like skin or muscle energy flux densities of 0.05-0.15 mJ/mm 2 have been used (Nishida et al, 2004;Aicher et al, 2006;Meirer et al, 2007). On the other hand, damages due to shock waves have been described to be caused by energy flux densities of 0.47 mJ/ mm 2 and higher (Delius et al, 1995;Ikeda et al, 1999;Wang et al, 2002;Mayer-Wagner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%